2007
DOI: 10.2134/jeq2007.0167
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Ammonia Emissions from a Cattle Feedlot using a Dispersion Model

Abstract: Livestock manure is a significant source of ammonia (NH3) emissions. In the atmosphere, NH3 is a precursor to the formation of fine aerosols that contribute to poor air quality associated with human health. Other environmental issues result when NH3 is deposited to land and water. Our study documented the quantity of NH3 emitted from a feedlot housing growing beef cattle. The study was conducted between June and October 2006 at a feedlot with a one-time capacity of 22,500 cattle located in southern Alberta, Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 23 publications
4
39
1
Order By: Relevance
“…Laubach et al (2008) clearly describe three paddockscale micrometeorological methods for measuring emissions from beef cattle. Specifically, one methodology based on inverse dispersion (Flesch et al, 2005) has been shown to have potential for estimating CH 4 emissions from feedlot and grazing production systems Kelliher, 2005a and2005b;McGinn et al, 2007 andLoh et al, 2008). This methodology has now been used across a number of grazing systems in northern Australia to determine herd-scale CH 4 emissions.…”
Section: Beef Cattle Ch 4 Emissions In Tropical Pasturesmentioning
confidence: 99%
“…Laubach et al (2008) clearly describe three paddockscale micrometeorological methods for measuring emissions from beef cattle. Specifically, one methodology based on inverse dispersion (Flesch et al, 2005) has been shown to have potential for estimating CH 4 emissions from feedlot and grazing production systems Kelliher, 2005a and2005b;McGinn et al, 2007 andLoh et al, 2008). This methodology has now been used across a number of grazing systems in northern Australia to determine herd-scale CH 4 emissions.…”
Section: Beef Cattle Ch 4 Emissions In Tropical Pasturesmentioning
confidence: 99%
“…It is considered to be currently among the most accurate micrometeorological techniques to calculate dispersion and determine emission rates (Denmead, 2008;Laubach, 2010;Loubet et al, 2010). It has been applied to assess methane and/or NH 3 emissions from agricultural fields fertilised with slurry (Sanz et al, 2010) and urea (Sommer et al, 2005), grazed fields (Denmead et al, 2004;Laubach and Kelliher, 2005;Laubach et al, 2008;Laubach, 2010), cattle feedlots McGinn et al, 2007;van Haarlem et al, 2008;Loh et al, 2008), and even complete farms (Flesch et al, 2009). The bLS calculates emissions accurately provided homogeneously emitting source areas (or well represented point sources), a precise monitoring of c bgd and a largely undisturbed wind field, i.e.…”
Section: Uncertainty Of the Bls/ftir Approachmentioning
confidence: 99%
“…Several filtering parameters were used to eliminate data when the bLS method (based on the MoninObukhov Similarity Theory) was known to under perform (McGinn et al 2007). The data that were retained for running WindTrax passed the following criteria:…”
Section: Measurements and Modeling At The Lagoonmentioning
confidence: 99%